2020
DOI: 10.3389/fimmu.2020.01622
|View full text |Cite
|
Sign up to set email alerts
|

B-Cell Activating Factor Secreted by Neutrophils Is a Critical Player in Lung Inflammation to Cigarette Smoke Exposure

Abstract: Cigarette smoke (CS) is the major cause of chronic lung injuries, such as chronic obstructive pulmonary disease (COPD). In patients with severe COPD, tertiary lymphoid follicles containing B lymphocytes and B cell-activating factor (BAFF) overexpression are associated with disease severity. In addition, BAFF promotes adaptive immunity in smokers and mice chronically exposed to CS. However, the role of BAFF in the early phase of innate immunity has never been investigated. We acutely exposed C57BL/6J mice to CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Research related to autoimmune hepatitis (AIH) has shown that serum BAFF levels are significantly higher in patients with AIH, compared to hepatitis patients and healthy controls, with positive correlations to AST, ALT, TBIL, and soluble CD30, implying BAFF contributes to liver injury in patients with AIH ( 26 ). BAFF expression was significantly higher in small pulmonary artery endothelial cells, alveolar epithelial cells, and alveolar macrophages in COPD patients, while circulating BAFF concentrations were higher in patients who smoked compared to non-smokers, suggesting that BAFF was associated with impaired lung function, hypoxia severity in COPD patients ( 27 29 ). We previously found elevated BAFF in serum, stool and colon tissue of adults with ulcerative colitis and Crohn’s disease, and serum BAFF levels correlated with disease activity, ESR, TNF-α, and IL-1β in ulcerative colitis patients ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research related to autoimmune hepatitis (AIH) has shown that serum BAFF levels are significantly higher in patients with AIH, compared to hepatitis patients and healthy controls, with positive correlations to AST, ALT, TBIL, and soluble CD30, implying BAFF contributes to liver injury in patients with AIH ( 26 ). BAFF expression was significantly higher in small pulmonary artery endothelial cells, alveolar epithelial cells, and alveolar macrophages in COPD patients, while circulating BAFF concentrations were higher in patients who smoked compared to non-smokers, suggesting that BAFF was associated with impaired lung function, hypoxia severity in COPD patients ( 27 29 ). We previously found elevated BAFF in serum, stool and colon tissue of adults with ulcerative colitis and Crohn’s disease, and serum BAFF levels correlated with disease activity, ESR, TNF-α, and IL-1β in ulcerative colitis patients ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, BAFF secretion was increased in neutrophils treated with cigarette smoke extract. Accordingly, the depletion of neutrophils reduces BAFF expression in the lung, and mice that are deficient in BAFF have decreased neutrophil infiltration in the lung [ 24 ]. Rheumatoid arthritis (RA) is characterized by the presence of rheumatoid factors and anti-citrullinated protein antibodies (ACPAs) in human serum [ 25 ].…”
Section: Neutrophil Networkmentioning
confidence: 99%
“…Exaggerated or dysregulated B cell function can drive T2 mucosal inflammatory states in nasal mucosa via local antibody production and other inflammatory cell recruitment [32]. BAFF is expressed on several immune and nonimmune cells and acts as a crucial biomolecule in sustaining B cell homeostasis [16,33]. Previous studies found that BAFF overexpressed peripheral blood and local tissues in tumor, inflammatory, and autoimmune diseases, and soluble form of BAFF was demonstrated to be a promising biomarker in reflecting disease activity and predicting prognosis [14,17,21,33].…”
Section: Discussionmentioning
confidence: 99%